1998
DOI: 10.1212/wnl.50.5.1273
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin G reduces MRI activity in relapsing multiple sclerosis

Abstract: We wanted to assess whether intravenous immunoglobulin G (IVIG) decreases disease activity on MRI in relapsing MS. Previous trials of IVIG in relapsing-remitting MS demonstrated a reduction of acute relapses, but these studies did not include MRI. We treated 26 patients in a randomized, double-blind, crossover study of IVIG 1 g/kg daily or placebo on 2 consecutive days every month during two 6-month treatment periods. The primary end point was the number of gadolinium-enhancing lesions on monthly serial MRI. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0
9

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(137 citation statements)
references
References 19 publications
3
125
0
9
Order By: Relevance
“…In RR-MS patients, relapse is inhibited by IVIg administration during remission [7][8][9][10]. The mechanism of action by which IVIg exerts this effect has not been elucidated, although several theories have been put forth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In RR-MS patients, relapse is inhibited by IVIg administration during remission [7][8][9][10]. The mechanism of action by which IVIg exerts this effect has not been elucidated, although several theories have been put forth.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous immunoglobulin (IVIg) has been reported to be an effective treatment for several autoimmune diseases [1][2][3][4][5][6][7][8][9][10]. In autoimmune diseases, IVIg may exert a therapeutic effect via multiple mechanisms, including the neutralization of autoantibodies with anti-idiotype antibodies [11], inhibition of complement-mediated damage [12,13], inhibition of inflammatory cytokine production by activated lymphocytes [14,15] and Fc receptor-mediated inhibition of inflammation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several double-blind, placebo-controlled trials with IVIg have shown some efficacy in MS (18,36,37). Polyclonal human IgM, sHIgM22, and sHIgM46 all enhanced CNS remyelination in the TMEV model as well as IVIg, suggesting that these Abs may be as effective in MS. Human mAbs that bind to OLs may have the additional benefit of direct OL stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies in MS indicate that IVIg may be partially effective in stabilizing the disease course (18,36,37). To determine whether IVIg could promote remyelination in the TMEV model of MS, chronically infected mice were treated with a single i.p.…”
Section: Ivig and Polyclonal Human Igm Promote Cns Remyelination In Tmentioning
confidence: 99%
“…However, the latter provide a more robust assessment of therapeutic e¡ect (McFarland et al 1992;Nauta et al 1994), as the former are more susceptible to the e¡ects of selection bias and regression to the mean. Numerous positive trials using crossover and parallel group designs have been reported (Moreau et al 1994;IFNB Study Group 1995;Jacobs et al 1996;Stone et al 1995;PRISMS 1998;European Study Group 1998;Edan et al 1997;Andersen et al 1996;Karussis et al 1996;Sorensen et al 1998;Durelli et al 1994;Mancardi et al 1998;Tubridy et al 1999) (table 1).…”
mentioning
confidence: 99%